Does policy uncertainty affect mergers and acquisitions? - Bonaime, Alice; Gulen, Huseyin; Ion, Mihai (Journal of Financial Economics, 2018)
Political and regulatory uncertainty is strongly negatively associated with merger and acquisition activity at the macro and firm levels. The strongest effects are for uncertainty regarding taxes, government spending, monetary and fiscal policies, and regulation. Consistent with a real options channel, the effect is exacerbated for less reversible deals and for firms whose product demand or stock returns exhibit greater sensitivity to policy uncertainty, but attenuated for deals that cannot be delayed due to competition and for deals that hedge firm-level risk. Contractual mechanisms (deal premiums, termination fees, MAC clauses) unanimously point to policy uncertainty increasing the target’s negotiating power.